Powrót do archiwum. Etnologiczna lektura metryk Kościoła rzymskokatolickiego - Latocha, Sebastian (Zeszyty Wiejskie, 2014)
Church registers seem to be a tedious lecture – wordy in form but with terse content, interesting only for genealogy enthusiasts who investigate their family trees. This stereotype cause lack of appliance of church registers in ethnology, despite their significance in describing our culture, daily life, rites and imagination figures that have become lost or remained up-to-date in actual manifestations. Ethnological reflection on church registers is a part of microhistory that illustrate history of mankind and its culture in cases. Church registers demonstrate our heritage, document local socio-cultural patterns and they are the source of identity of modern man. In outline I present the results of research into church registers carried out by ethnologist with regard to documents from Roman Catholic parish in Lubania from years 1849–1867.